2007
DOI: 10.1027/0227-5910.28.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Suicidal Ideations Through the Realization of Meaningful Personal Goals

Abstract: A personal goal intervention program was offered to early retirees aged 50 to 65 years with the objective of increasing their subjective well-being. The program was aimed at helping the participants set, plan, pursue, and realize their personal goals. A subsample of 21 participants with suicidal ideas was identified from a larger sample (N = 354) of retirees living in the community who took part in the study to evaluate the program. The experimental (n = 10) and control (n = 11) groups were compared on their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 56 publications
0
57
0
1
Order By: Relevance
“…That is, a gritty individual shows consistent interest in a goal (passion) and works toward this goal consistently (perseverance). While other stability-related factors (such as conscientiousness and self-control) have been studied as buffers to suicide (Lapierre et al, 2007), the construct of grit represents a unique facet of personality that may be especially adept at buffering against negative life events. Although similar, conscientiousness and self-control both represent shorter-term goal orientations than grit (Duckworth and Gross, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…That is, a gritty individual shows consistent interest in a goal (passion) and works toward this goal consistently (perseverance). While other stability-related factors (such as conscientiousness and self-control) have been studied as buffers to suicide (Lapierre et al, 2007), the construct of grit represents a unique facet of personality that may be especially adept at buffering against negative life events. Although similar, conscientiousness and self-control both represent shorter-term goal orientations than grit (Duckworth and Gross, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, PP exercises, including those focusing on gratitude, mindfulness and using strengths, have led to (often persistent) improvements in mood symptoms in patients with depressive symptoms [19,23,24], and a prior intervention on meaningful goals in older adults with suicidal thoughts led to greater self-efficacy and psychological well-being [25].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary findings demonstrated a significant reduction in suicide ideation, the wish to die, and depressive symptom severity ; complete study findings additionally demonstrated a significant improvement in MIL and enhanced psychological well-being over the course of treatment (Heisel et al submitted). Although not grounded in existential theory, two quasi-experimental intervention studies, of integrated reminiscence and narrative therapies for depressed older adults (Bohlmeijer et al 2008) and a cognitive-behavioral group designed to train early retirees to set, plan, and pursue meaningful goals, showed posttreatment increases in psychological wellbeing, yet no between-group increases in MIL or PIL (Lapierre et al 2007). These findings collectively indicate that psychological interventions attending to existential factors can enhance mental health and well-being, enhance perceptions of MIL, and may ultimately help reduce or resolve suicide ideation and the wish to die.…”
Section: Discussionmentioning
confidence: 96%